2003
DOI: 10.1016/s0741-5214(03)00934-0
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of endovascular tube graft repair of thoracic aortic aneurysm: midterm follow-up and lessons learned

Abstract: While promising, this midterm experience with commercially available devices highlights the shortcomings of current stent-graft technology. Three significant advancements are required to fulfill the potential of this important treatment method: a stent graft with a durable proximal and distal fixation device, enhanced engineering to accommodate high thoracic aortic fatigue forces, and a mechanism to adapt to aortic arch and visceral segment branches to enable treatment of lesions that extend to or include thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(92 citation statements)
references
References 11 publications
5
81
0
6
Order By: Relevance
“…This technique has the advantage of being far less invasive than surgery, with potentially fewer postoperative complications and lower morbidity. Ellozy et al 29 recently reported a series of 84 patients receiving endovascular stent-grafts to treat descending thoracic aortic aneurysms. Primary technical success was achieved in 90%, and successful exclusion of the aneurysm was achieved in 82%.…”
Section: Descending Thoracic Aortic Aneurysmsmentioning
confidence: 99%
“…This technique has the advantage of being far less invasive than surgery, with potentially fewer postoperative complications and lower morbidity. Ellozy et al 29 recently reported a series of 84 patients receiving endovascular stent-grafts to treat descending thoracic aortic aneurysms. Primary technical success was achieved in 90%, and successful exclusion of the aneurysm was achieved in 82%.…”
Section: Descending Thoracic Aortic Aneurysmsmentioning
confidence: 99%
“…Esta complicaci贸n ha sido reportada ocasionalmente en el manejo endovascular electivo de aneurismas de la aorta descendente, con mucha menor frecuencia que en la cirug铆a abierta 12,13 . Incluso en series recientes de reparaci贸n endovascular de lesiones aneurism谩ticas en general, no se reportan casos de paraplejia 16,[24][25][26] o incidencias inferiores a 2,5% 27,28 . En la presente serie, aunque peque帽a, no tuvimos que lamentar esta devastadora complicaci贸n.…”
Section: Discussionunclassified
“…[35] The rates of endoleak reported in literature vary and depend upon the type of pathology treated, and the length of the follow-up. Parmer et al [36] reported an endoleak incidence of 29% at an average follow-up of 17 months, Ellozy et al [37] published an incidence of 18% at roughly 15 months, and the Gore-TAG trial [38] reported only 10.6% at 5 years.…”
Section: Endoleakmentioning
confidence: 99%
“…Other smaller experiences in literature with follow-ups ranging from 15 -40 months presented a percentage of rupture at a distance between 1.6% and 6%. [37,43,44] …”
Section: Aneurysm Rupturementioning
confidence: 99%